Tantangan dan Strategi Polri Dalam Penanggulangan Kejahatan di Masa Pademi Kajian Perspektif Politik Kriminal - Wahyuningrum, Kartika Sasi; Irawan, Agus; Alendra, Alendra; Kurniawan, Ridha (Universitas Batanghari Jambi, 2023)
The police are said to be the front guard which has one of the duties and authorities, namely to protect the public in all situations and conditions, especially during the Covid-19 pandemic. The increase in crime rates during the pandemic and PSBB was due to the increasingly weakening economic situation. So the National Police, which has the duty and authority to safeguard society, must provide safe conditions in the current pandemic situation. To achieve this safe condition, the National Police found new challenges and strategies in dealing with crime during the pandemic. The research approach used in this research is the juridical-empirical method, which is a type of legal research that analyzes and examines the operation of law in society. The type of legal research used is descriptive, namely research that aims to describe something in an area at a certain time. This research shows that the challenges faced by the National Police in the pre-pandemic era were classic challenges so that the strategies used were also classic. This is different from the challenges and strategies used during the pandemic which prioritized Polri's humanism and the use of technology in investigations and inquiries